Towards the first plasma-electron screening experiment - Casey, Daniel T.; Weber, Chris R.; Zylstra, Alex B.; Cerjan, Charlie J.; Hartouni, Ed; Hohenberger, Matthias; Divol, Laurent; Dearborn, David S.; Kabadi, Neel; Lahmann, Brandon; Gatu Johnson, Maria; Frenje, Johan A. (Frontiers in Physics, 2023)
The enhancement of fusion reaction rates in a thermonuclear plasma by electron screening of the Coulomb barrier is an important plasma-nuclear effect that is present in stellar models but has not been experimentally observed. Experiments using inertial confinement fusion (ICF) implosions may provide a unique opportunity to observe this important plasma-nuclear effect. Herein, we show that experiments at the National Ignition Facility (NIF) have reached the relevant physical regime with respect to the density and temperature conditions but the estimated impacts of plasma screening on nuclear reaction rates are currently too small and need to be increased to lower the expected measurement uncertainty. Detailed radiation hydrodynamics simulations show that practical target changes, like adding readily available high-Z gases, and significantly slowing the inflight implosion velocity while maintaining inflight kinetic energy, might be able to push these conditions to those where plasma screening effects may be measurable. We also perform synthetic data exercises to help understand where the anticipated experimental uncertainties will become important. But challenges remain such as detectability of the reaction products, non-thermal plasma effects, species separation, and impacts of spatial and temporal gradients. This work lays the foundation for future efforts to develop an important platform capable of the first plasma electron screening observation.